A Study on Difference in Short-Term Memory in Healthy Males and Females of Kerala - Kumar, Sailesh Sai; Jissa, George; Mukkadan, JK (Journal of Nobel Medical College, 2013)
Journal of Nobel Medical College Vol. 2, No.2 Issue 4 May-October 2013 Page 57-61 DOI: http://dx.doi.org/10.3126/jonmc.v2i2.8807